Diversity of Soil Fungi in Different Land Use Types in Tha Kum-Huai Raeng Forest Reserve, Trat Province - Pongsatorn Puangsombat,; Uthaiwan Sangwanit,; Dokrak Marod, (Agriculture and Natural Resources, 2010)
The soils collected from five land use types located in the Tha Kum-Huai Raeng Forest Reserve, Trat province were studied with two objectives: 1) to assess and compare the composition, abundance and diversity of soil fungi; and 2) to relate the fungal diversity with leaf litter dry weight and soil physical and chemical properties. The five land use types were: secondary dry evergreen forest (DEF), Phayoong (Dalbergia cochinchinensis) plantation (PP), grassland (GL), rubber (Hevea brasiliensis) plantation (RP) and a pineapple field (PF). The soil collection was carried out in the rainy season by establishing a sample plot of 100×100 m in each land use type and nine soil samples were taken from 0-10 cm soil depth. Before a soil sample was taken, the leaf litter covering the soil in a plot 1×1m was scraped and put into a plastic bag. The litter samples were dried and measured for dry weight. Each soil sample was analyzed for soil physical and chemical properties and isolated for soil fungi using the soildilution plate method. The emerging fungal colonies were counted for numbers and identified to the species level based on morphological characteristics. A total of 28 genera and 71 species of soil fungi were identified from the DEF, PP, GL, RP and PF soils. They belonged to the Class Zygomycetes (4 genera and 4 species), the Class Ascomycetes (4 genera and 5 species) and the Class Deuteromycetes (20 genera and 62 species) and most of them were organic matter decomposers. Some soil fungi appeared in all land use types, but some appeared only in a few land use types or in as little as one. The land use type which had the highest Shannon-Wiener’s diversity index of soil fungi was PF, followed by DEF, PP, GL and RP, respectively. The highest similarity of fungal community composition between two land use types calculated by Sorensen’s index of similarity occurred between DEF and PP, followed by PP and GL, and then DEF and GL, while the lowest similarity index value was between PF and RP. The analysis of variance of mean values of soil environmental factors, including leaf litter dry weight and soil chemical and physical properties, among the five land use types revealed that the soils were significantly different from each other. The relationships of soil fungi with all the mentioned soil environmental factors analyzed by the ordination method with canonical correspondence analysis (CCA) showed that some soil fungi related positively with the P, Ca and Mg contents in soils. It is recommended that the five land use types should be properly managed, so that there are no abrupt changes in their soil environmental conditions, in order to keep the existing diversity of soil fungi.